Relation of seminal plasma hormonal levels with quality of frozen semen in cattle - KUMAR, SATISH; SRIVASTAVA, SUSHANT (The Indian Journal of Animal Reproduction, 2023)
Levels of seminal plasma Testosterone, Tri-iodo-thyronine {T3) and Thyroxin {T4) in the fresh ejaculatetwere estimated aild its correlation with post thaw seminal quality was found out. The levels of these honnoneswere significantly_ {p
Keywords: Testosterone; Thyroid hormones; Semen; Freezing; Sperm penetration distance; Hypo-osmot swelling test